2016
DOI: 10.1007/s11665-016-2297-8
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Electrical Conductivity of the Liquid Sn-3.8Ag-0.7Cu Alloy with Minor Co Admixtures

Abstract: The viscosity and electrical conductivity as structure-sensitive transport properties of the liquid metals and alloys are important for modeling of the melting and solidification processes. The viscosity and electrical conductivity data provide additional information about the influence of impurities on the structure and physicochemical properties of the liquid metal matrix, which is useful for understanding of structural transformations in the liquid state. In the present work, an impact of minor Co admixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…The viscosity of liquid phase is taken in accordance to Ref. [27], whereas solid phases are chosen as regions of very high viscosities [25]. The free energy of the system is defined as the volume integral of free energy density [28]: The free energy densities of Cu, Sn and IMC (η) phases at 250 • C are numerically evaluated in accordance to the values presented in Fig.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…The viscosity of liquid phase is taken in accordance to Ref. [27], whereas solid phases are chosen as regions of very high viscosities [25]. The free energy of the system is defined as the volume integral of free energy density [28]: The free energy densities of Cu, Sn and IMC (η) phases at 250 • C are numerically evaluated in accordance to the values presented in Fig.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…(10 equations describing its dependence on temperature are collected in Table 7 for all studied models. As an example, Fig.…”
Section: Density In the Liquid Sn-ag-cu Ternary Alloysmentioning
confidence: 99%
“…It is also expected that metal nanoparticles will be dissolved during the soldering process and their atoms will replace the Cu atoms in the Cu-Sn IMCs, directly impacting their morphology and the growth rate of the IMCs, while solid metal (M) additions in bulk could chemically react with the liquid Sn-based matrix and form M-Sn IMCs instead. Recently, several efforts have been made to develop a new generation of Pb-free solders by minor additions of various nanosized impurities, such as ceramic or metal nanoparticles, into commercial SAC solders [9][10][11][12][13]. It was shown that the TiO 2 particles were incorporated at the Sn grain Metals 2023, 13, 1093 2 of 10 boundaries in reinforced 99Sn0.3Ag0.7Cu-TiO 2 composite solders at both the interface of the intermetallic layer and in the solder bulk [10].…”
Section: Introductionmentioning
confidence: 99%
“…The transport properties and microstructure of the liquid SAC alloys with Co impurities were investigated in Ref. [12], while the extra heat effects of nanosized Ni addition into the liquid Sn-3.8Ag-0.7Cu (SAC387) solder compared to the bulk material were investigated in Ref. [13].…”
Section: Introductionmentioning
confidence: 99%